EDUCATION AND ACTION FOR SINGLE-USE PLASTIC REDUCTION IN PUBLIC SPACES: A COMMUNITY SERVICE PROGRAM AT MALANG CITY SQUARE - Amanda Arifaturrofiqoh; Balqis Nurul Aini; Putra, Rivandi Pranandita; Muhammad Janwar; Regina Aura Rosalia; Ria Ginarti Anjana Putri; Vita Ayu Kusuma Dewi (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
Single-use plastic waste continues to pose a significant environmental challenge in urban public spaces across Indonesia, including in the Alun-Alun area of Malang City, East Java Province, Indonesia. The concentration of socio-economic activities in this location contributes to elevated levels of plastic consumption, particularly from the informal sector such as street vendors. Compounding this issue is the generally low level of public awareness regarding the environmental consequences of plastic pollution. This community engagement initiative was designed to enhance environmental literacy and promote behavioural change through direct educational outreach and the provision of reusable cloth bags as a sustainable alternative. Employing a participatory and educational methodology, the programme commenced with field-based observation to assess plastic usage habits, followed by the development and dissemination of educational brochures and the direct distribution of cloth bags to local residents and informal sector actors. The public response indicated a high degree of receptivity and engagement, as demonstrated by active participation in discussions and immediate adoption of the alternative bags. Preliminary post-activity evaluation revealed improved comprehension of the environmental impacts of single-use plastics and a greater willingness to transition towards more sustainable consumption practices. This initiative demonstrates that education-based interventions, when supported by practical solutions, can effectively cultivate ecological awareness and stimulate community-level environmental action. Furthermore, it contributes to the realisation of several Sustainable Development Goals (SDGs), particularly SDG 3 (Good Health and Well-being), SDG 12 (Responsible Consumption and Production), SDG 13 (Climate Action), SDG 14 (Life Below Water), and SDG 15 (Life on Land).